Basic kitchen preparation [videorecording] (ProChef training materials, 2006)
Everything you do in a kitchen is made up of several small steps. Some of these steps are done every day, while others are done only once in awhile. None of these steps will lead you to a finished product, but they do give you something that will be used in a larger recipe. It's all about the basics, and correct preparation is the key.